Ophiocordyceps sinensis preparations combined with the renin–angiotensin system inhibitor for diabetic kidney disease treatment: an umbrella review of systematic reviews and network meta-analysis - Xue, Xue; Jin, Xin-Yan; Ye, Xing-Lan; Li, Ke-Ying; Li, Jia-Xuan; Liu, Xue-Han; Bai, Juan; Liu, Qiang; Zhang, Bing-Rui; Zou, Xin-Rong; Yuan, Jun; Lu, Chun-Li; et al. (Frontiers in Pharmacology, 2024)
Aims: This study aimed to synthesize the evidence of the comparative effectiveness and safety of Ophiocordyceps sinensis (OS) preparations combined with renin–angiotensin system inhibitors (RASi) for diabetic kidney disease (DKD). Methods: Eight databases were searched from their inception to May 2023. Systematic reviews (SRs) of OS preparations combined with RASi for DKD were identified. Randomized controlled trials (RCTs) from the included SRs and additional searching were performed for data pooling. Cochrane risk-of-bias 2 (RoB 2) tool and AMSTAR 2 were used to evaluate the methodological quality of RCTs and SRs, respectively. A Bayesian network meta-analysis was performed to compare the add-on effect and safety of OS preparations for DKD. The certainty of evidence was graded using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Results: Fourteen SRs were included, whose methodological quality was assessed as high (1/14) or critically low (13/14). After combining additional searching, 157 RCTs were included, involving 13,143 participants. The quality of the RCTs showed some concerns (155/157) or high risk (2/157). Jinshuibao capsules and tablets, Bailing capsules and tablets, and Zhiling capsules were evaluated. Compared to RASi, adding either of the OS capsular preparations resulted in a decreased 24-h urinary total protein levels. OS preparations ranked differently in each outcome. Jinshuibao capsules plus RASi were beneficial in reducing urinary protein, serum creatinine, serum urea nitrogen, and blood glucose levels, with moderate-certainty evidence. No serious adverse events were observed after adding OS to RASi. Conclusion: Combining OS capsular preparations with RASi appeared to be associated with decreased urinary total protein levels in DKD patients. Further high-quality studies are needed to confirm. Systematic Review Registration: INPASY202350066.